MODUS KALIMAT PERINTAH DAN LARANGAN DALAM “ASBAB WURUD AL-HADITS” KARYA IMAM SUYUTHI KAJIAN PRAGMATIK - Ahmad Jazuli (Arabic Literature Department, 2019)
This article aims to explain the commands and prohibitions of the prophet Muhammad in hadits by using Searle's speech act theory. The purpose of this study focused to describe the commands and prohibitions of the prophet Muhammad in seen from sentence mode. Results of this study indicate that there are several characteristics of the use of the phrase mode commands and prohibitions of the Prophet Muhammad such us declarative sentences mode with verb sentence form and noun sentence form; Imperative sentences mode with fi‘lul-amri form, ismu fi‘lil-amri form, dan la an-nahiyah form; and the interrogative sentences mode with using “َ ”أand “.”